Pollination Biology of Potentilla recta (Sulfur Cinquefoil) and Its Cooccurring Native Congener Potentilla gracilis in Northeastern Oregon - James McIver; Karen Erickson (Psyche: A Journal of Entomology, 2012)
Pollination biology of the invasive plant sulfur cinquefoil (Potentilla recta L.) and it's native cooccurring congener slender cinquefoil (P. gracilis Dougl. ex. Hook.) was studied from 2002–2004, at four sites in northeastern Oregon, USA The native cinquefoil flowered first for five weeks, followed by the invasive for five weeks, with two weeks overlap in mid-June. Invasive flowers attracted 74 species and 543 individuals; the native attracted 93 species and 619 individuals. The most important pollinators for the invasive, in order of importance, were: Apis mellifera, Ceratina nanula, Halictus tripartitus, Lasioglossum sisymbrii, and Bombus rufocinctus; for the native: C. nanula, Trichodes ornatus, H. ligatus, L. sisymbrii, and L. olympiae. The invasive produced higher numbers of seeds per plant, having greater mass per unit vegetation. Mean seed size was lower for the invasive when pollinators were allowed access to flowers, but seed size increased linearly with more complete exclusion of pollinators; the native showed no such response to pollinator exclusion. Compared to the native, nearly twice as many seeds germinated for sulfur cinquefoil (35.0% versus 19.5%), with seeds germinating over a longer period of time. Results are discussed as they relate to the invasiveness of sulfur cinquefoil relative to the native.